Effect of Artificial Insemination Time on the Fertility of Layer Hens - Saleh, DM; Sugiyatno, Sugiyatno (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
A study on the effect of AI time on the fertility of layer hens was carried out. Semen was collected from eight kampung roosters, with age ranging from 12-18 months.Â Completely Randomized Design was used to analyze the data obtained.Â Every eight hens (n=8) was inseminated intravaginally at 0-2 hrs, >2-4 hrs, > 4-6 hrs and >6-8 hrs after oviposition.Â The results showed that insemination time did not affectÂ (P>0.05) the percentage of fertility from days 2 to 20.Â However, the insemination time affected (P<0.05) the percentage of fertile eggs from days 2 to 9 and it did not affect (P>0.05) the mean duration of the fertile period.Â In conclusion, the time of insemination at 0 â 2 hours after oviposition gave the best fertility.Â It is recommended that for the best fertility flock inseminations should be performed at a time of 0-2 hours after an egg is laid every 9 days. (Animal Production 8(2): 83-87 (2006)Â Key Words: Kampung roosters, semen, fertility, fertile period, AI time